Exploring the Dynamics of Work Satisfaction and Innovation Among Young Lecturers in Post-Pandemic Indonesia - Dara, Despinur; Saparuddin, Saparuddin (Journal of Indonesian Economy and Business, 2025)
Introduction/Main Objectives: This study purposes to investigate the complex relationship among work autonomy, work crafting, work satisfaction, and innovative work behaviour. Background Problems: How autonomy, crafting, and work satisfaction relate and, more collectively, affect young lecturers' innovative work behaviours within the shifting educational circumstances in Indonesia is a major concern. Novelty: This research has groundbreaking importance because it applies the self-determination theory to this particular academic context of Indonesia. It emphasises the impact of cultural variations on the motivation and behaviour of young lecturers. It offers an innovative perspective on how young lecturers may be innovative and adaptable in the face of pedagogical and technical changes that are occurring at a fast rate. Research Methods: The study uses a mixed method approach in which 382 young lecturers from state universities in Indonesia participate in surveys, in-depth interviews, and participatory observations. By using structural equation modelling (SEM) by Lisrel and systematically coded by NVIVO, it becomes possible to analyse the complex interrelationships between the variables. Finding/Result: Work crafting on work satisfaction and work satisfaction on innovative behaviour has a significant positive impact. In contrast, work autonomy has no significant influence on lecturer work satisfaction. Excessive autonomy and interference without assistance will lower lecturer work satisfaction. In a dynamic educational environment, encouraging young lecturers to use creative teaching techniques and having institutional support can boost their creativity. Conclusion: What is brought into sharp focus through this study is the balance of autonomy with adequate support for young lecturers in a world that is rapidly developing in terms of digital education. Thus, pressure exists in universities to ensure young lecturers enjoy convenience in their work and support them to ensure they obtain the institutional support and work tools required in the digital era.